2010
DOI: 10.1007/s00203-010-0602-8
|View full text |Cite
|
Sign up to set email alerts
|

CspC and CspD are essential for Caulobacter crescentus stationary phase survival

Abstract: The cold shock response in bacteria involves the expression of low-molecular weight cold shock proteins (CSPs) containing a nucleic acid-binding cold shock domain (CSD), which are known to destabilize secondary structures on mRNAs, facilitating translation at low temperatures. Caulobacter crescentus cspA and cspB are induced upon cold shock, while cspC and cspD are induced during stationary phase. In this work, we determined a new coding sequence for the cspC gene, revealing that it encodes a protein containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 49 publications
2
18
0
3
Order By: Relevance
“…The cspA, cspC, and cspD mutant strains were constructed previously (4,31). cspB mutant and cspA cspB double mutant strains were obtained by allelic replacement using the NA1000 and cspA mutant strains, respectively, as background.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cspA, cspC, and cspD mutant strains were constructed previously (4,31). cspB mutant and cspA cspB double mutant strains were obtained by allelic replacement using the NA1000 and cspA mutant strains, respectively, as background.…”
Section: Methodsmentioning
confidence: 99%
“…The C. crescentus genome contains four paralogues of csp genes, two of them (cspA and cspB) being cold induced, encoding proteins containing a single cold shock domain (CSD), and the other two (cspC and cspD) being stationary phase induced, encoding proteins with two CSDs (4,31). Recently, we demonstrated that stationary-phase induction of C. crescentus cspD is regulated by the levels of the second messenger ppGpp and by the SpdR/SpdS two-component system (7).…”
mentioning
confidence: 99%
“…Phenotypic analyses of cspC and cspD null mutants, as well as the deletion of both genes, showed that cell viability is severely decreased in the cspC and cspCD mutants upon entry into stationary phase (3). The cspC cells show aberrant morphology at stationary phase, and this phenotype is more severe in the double mutant, suggesting that cspD can at least in part compensate for the lack of cspC (3).…”
mentioning
confidence: 99%
“…This suggests that a mechanism must be in place to promote hypercurvature in stationary phase cells that is in addition to inhibition of division through reduced FtsZ levels. Caulobacter cells in stationary phase differentially regulate expression of many genes to promote survival and, perhaps, morphological changes through transcriptional regulators such as SpdR [98100]. …”
Section: Shapeshifting During Environmental Stressmentioning
confidence: 99%